A Model Aided Inertial Navigation System for Automatic Landing of Unmanned Aerial Vehicles. Issue 2 (3rd June 2018) - Mohammadkarimi, Hamed; Nobahari, Hadi
Abstract: The use of Model Aided Inertial Navigation (MAIN) during the landing of an Unmanned Aerial Vehicle (UAV) is investigated. A new MAIN algorithm is proposed, which is fast and accurate enough to be used in automatic landing. In this algorithm, the six Degree of Freedom (6DoF) model of the UAV is tightly coupled with the inertial navigation system; thus, the 6DoF model acts as an aiding system for the INS and vice versa. In the last parts of the landing phase in proximity of Earth, the proposed algorithm also estimates and removes the Ground Effect (GE) uncertainties and provides the height controller with a realistic model. An adaptive controller based on a parametric state‐space model is used to adjust the height controller gains as the flight condition changes due to GE. Simulation results show that the proposed algorithm provides sufficient accuracy for automatic landing of UAVs. Copyright © 2018 Institute of Navigation